Application of dual energy method for non-destructive testing of materials designed to work in extreme conditions - Chakhlov S. V. Sergey Vladimirovich; Wang Yanzhao; Osipov S. P. Sergey Pavlovich; Udod V. A. Viktor Anatolievich (2017, 2017)
Title screen